A scoping review of feasibility, cost, access to rehabilitation services and implementation of telerehabilitation: Implications for low- and middle-income countries. (October 2022) - Nizeyimana, Eugene; Joseph, Conran; Plastow, Nicola; Dawood, Gouwa; Louw, Quinette A
Objective: To scope all published information reporting on the feasibility, cost, access to rehabilitation services, implementation processes including barriers and facilitators of telerehabilitation (TR) in low- and middle-income countries (LMICs) and high-income countries (HICs). Methods: A comprehensive electronic search of PubMed, Scopus, PEDro, Cochrane library, EBSCOhost (Academic search premier, Africa-wide information, CINAHL, Eric, MEDLINE, Health sources - Nursing/Academic edition), Africa online, as well as ProQuest databases were conducted. To maximise the coverage of the literature, the reference lists of included articles identified through the search were also screened. The analysis included both descriptive summary and inductive thematic analysis. Results: Twenty-nine studies were included. TR was reported to be feasible, cost-saving and improved access to rehabilitation services in both HICs and LMICs settings. Asynchronous methods using different mobile apps (Skype, WhatsApp, Google meet, Facebook messenger, Viber, Face time and Emails) were the most common mode of TR delivery. Barriers to the implementation were identified and categorised in terms of human, organisational, technical and clinical practice related factors. Facilitators for health professionals and patients/caregivers' dyads were also identified. Conclusion: TR could be considered a feasible service delivery mode in both HICs and LMICs. However, the mitigation of barriers such as lack of knowledge and technical skills among TR providers and service users, lack of secure platform dedicated for TR, lack of resources and connectivity issues which are particularly prevalent in LMICs will be important to optimise the benefits of TR.